Antarctic aldehyde dehydrogenase from Flavobacterium PL002 as a potent catalyst for acetaldehyde determination in wine - V. I. Paun; R. M. Banciu; P. Lavin; A. Vasilescu; P. Fanjul-Bolado; C. Purcarea (Scientific Reports, 2022)
Abstract Latest solutions in biotechnologies and biosensing targeted cold-active extremozymes. Analysis of acetaldehyde as a relevant quality indicator of wine is one example of application that could benefit from using low-temperatures operating catalysts. In search of novel aldehyde dehydrogenases (ALDH) with high stability and activity at low temperatures, the recombinant S2-ALDH from the Antarctic Flavobacterium PL002 was obtained by cloning and expression in Escherichia coli BL21(DE3). Structural and phylogenetic analyses revealed strong protein similarities (95%) with psychrophilic homologs, conserved active residues and structural elements conferring enzyme flexibility. Arrhenius plot revealed a conformational shift at 30 °C, favoring catalysis (low activation energy) at lower temperatures. In addition to a broad substrate specificity with preference for acetaldehyde (Km = 1.88 mM), this enzyme showed a high tolerance for ethanol (15%) and several salts and chelators (an advantage for wine analysis), while being sensitive to mercury (I50 = 1.21 µM). The neutral optimal pH (7.5) and the stability up to 40 °C and after lyophilization represent major assets for developing S2-ALDH-based sensors. An enzymatic electrochemical assay was developed for acetaldehyde detection in wines with proven accuracy in comparison with the reference spectrophotometric method, thus evidencing the potential of S2-ALDH as effective biocatalyst for industry and biosensing.